2005
DOI: 10.1016/j.nimb.2005.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Laser photodetachment electron spectroscopy studies of heavy atomic anions

Abstract: Laser photodetachment electron spectroscopy (LPES) experiments have been performed at the Negative Ion Research Facility at the University of Nevada, Reno, using a crossed ion-laser beams apparatus to investigate the structure and dynamics of heavy atomic anions. A small ion accelerator is used to produce monoenergetic beams of negatively-charged atomic ions. Ejected electrons (photoelectrons), produced by the collision of the ions with linearly-polarized photons, are collected and their kinetic energy is meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
6
14
0
Order By: Relevance
“…Also, using the A values of O'Malley and Beck, capacitance scaling for f -filling lanthanide atoms follows the pattern observed in p-filling first and second row neutral atoms. Further, work by investigators [17][18][19] other than O'Malley and Beck favors the 6p electron attachments that occur in their lanthanide electron affinity calculations and that appear to be instrumental in producing the single capacitance scaling line seen in Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, using the A values of O'Malley and Beck, capacitance scaling for f -filling lanthanide atoms follows the pattern observed in p-filling first and second row neutral atoms. Further, work by investigators [17][18][19] other than O'Malley and Beck favors the 6p electron attachments that occur in their lanthanide electron affinity calculations and that appear to be instrumental in producing the single capacitance scaling line seen in Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…If all those anion attachments did not occur in such a simple manner, in the same orbital, the resulting capacitance scaling might not occur on a single line. There is some independent evidence from experiments [17,18] and from theory [19], however, that electron attachments to produce lanthanide anions in their ground states do take place in 6p orbitals. This argues further in favor of capacitance scaling along a single line, like that in Fig.…”
Section: Analysis and Predictionsmentioning
confidence: 99%
“…Measured EAs for atomic Eu [1,4], Tb [17], Tm [18], Nd [17] and Nb [6,9] are available and, except for Nb, have been compared with other data in [2]. It is noted that ref.…”
Section: Introductionmentioning
confidence: 99%
“…(1) In [2] it was concluded that both the measured and the calculated EAs for the lanthanide atoms Eu [4][5][6][7][8], Tb [9,10], Tm [11,12], Gd [5,10] and Nd [5,6,9], including the Nb [13][14][15][16] atom require reinterpretation. New recommended EA values for these atoms were presented.…”
Section: Introductionmentioning
confidence: 99%